Surgical Management and Histopathology of Bovine Papilloma - Renu; Bansal, Shailja; Mehra, Manisha; Jhirwal, Suresh Kumar; Meena, Abhay Kumar; Singh, Satyaveer (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
The present study was aimed to surgically manage and investigate papilloma in cattle by gross and histopathological examination. A five year old female non-descript cow with wart-like lesion on the mouth was examined and managed surgically.